THE EFFECT OF COMPENSATION, JOB STRESS AND WORK ENVIRONMENT ON JOB SATISFACTION - Nugroho, Dodit Cahyo; Manafe, Leonard Adrie (International Journal of Business, Law, and Education, 2023)
Human resources play an important role in the growth and development of a company or organisation. If employees are satisfy with their work, the company can easily develop and compete with other similar companies. The overall objective of this study was to determine the impact of compensation, stress and work environment on job satisfaction. Quantitative method was used for this research. Total sample of 66 respondents Perum Bulog employees. The results of instrument test, classic assumption are valid and reliable. The results of hypothesis testing show that Compensation, Work Stress, Work Environment partially and simultaneously have a significant and positive influence on job satisfaction.